From parastatals to private trade: Lessons from Asian agriculture - Rashid, Shahidur; Gulati, Ashok; Cummings, Jr., Ralph (International Food Policy Research Institute, 2008)
In developing countries across Asia, food marketing parastatals have played an important role in agricultural policy, especially with regard to government efforts to stabilize food prices. Three broad market failures constitute the primary arguments for this form of government intervention: a lack of market integration stemming from inadequate infrastructure, the absence or inadequacy of risk-mitigating institutions and markets, and the need to protect the world's poorest communities from a volatile global market. Opponents of such public intervention schemes claim that the old rationales are no longer convincing, that the programs are not cost-effective and do not allocate resources optimally, and that private institutions are strong enough to take over many of the functions traditionally performed by parastatals. In From Parastatals to Private Trade, the editors—clearly from the latter camp—pose three general questions: Why must parastatal-centered policies in Asia change, when should policy changes occur, and how should such change happen: gradually or abruptly? Experts in agricultural policy use case studies from South Asia (Bangladesh, India, and Pakistan) and East Asia (Indonesia, the Philippines, and Vietnam) to answer these questions; and a concluding chapter synthesizes these countries' experiences with price stabilization programs. In light of the evidence—which indicates that parastatals played important roles in the past but have become overly expensive, and that reduced intervention can promote competition, help develop alternative institutions, and release funds for development and antipoverty programs without jeopardizing price stability—the editors highlight the challenges ahead and propose suggestions for reforming the existing paradigm for price-related policies. This volume provides valuable analyses for anyone concerned with balancing government intervention with market-friendly policies.